Revisiting the taxonomy of Ophiorrhiza codyensis and lectotypification of O. pykarensis (Rubiaceae), two endemic taxa of the Western Ghats - Hareesh, Vadakkoot Sankaran; Preethamol, Sidhabhavan Nanjan; Sabu, Mamiyil; Thoppil, John Ernest (Phytotaxa, 2020)
Taxonomic identity and occurrence of Ophiorrhiza codyensis (Rubiaceae), a little known endemic species from the Western Ghats is discussed along with its rediscovery after a gap of 106 years outside from its type locality. Detailed description of the species is provided with colour photographs, ecology and conservation status. In addition, a lectotype is designated for O. pykarensis, another endemic species of the Western Ghats. A new occurrence of O. trichocarpon in the Western Ghats is also discussed.